Drosophila NOMPC is a mechanotransduction channel subunit for gentle-touch sensation. - Yan, Z.; Zhang, W.; He, Y.; Gorczyca, D.; Xiang, Y.; Cheng, L.E.; Meltzer, S.; Jan, L.Y.; Jan, Y.N. (Nature, 2013)
Touch sensation is essential for behaviours ranging from environmental exploration to social interaction; however, the underlying mechanisms are largely unknown. In Drosophila larvae, two types of sensory neurons, class III and class IV dendritic arborization neurons, tile the body wall. The mechanotransduction channel PIEZO in class IV neurons is essential for sensing noxious mechanical stimuli but is not involved in gentle touch. On the basis of electrophysiological-recording, calcium-imaging and behavioural studies, here we report that class III dendritic arborization neurons are touch sensitive and contribute to gentle-touch sensation. We further identify NOMPC (No mechanoreceptor potential C), a member of the transient receptor potential (TRP) family of ion channels, as a mechanotransduction channel for gentle touch. NOMPC is highly expressed in class III neurons and is required for their mechanotransduction. Moreover, ectopic NOMPC expression confers touch sensitivity to the normally touch-insensitive class IV neurons. In addition to the critical role of NOMPC in eliciting gentle-touch-mediated behavioural responses, expression of this protein in the Drosophila S2 cell line also gives rise to mechanosensitive channels in which ion selectivity can be altered by NOMPC mutation, indicating that NOMPC is a pore-forming subunit of a mechanotransduction channel. Our study establishes NOMPC as a bona fide mechanotransduction channel that satisfies all four criteria proposed for a channel to qualify as a transducer of mechanical stimuli and mediates gentle-touch sensation. Our study also suggests that different mechanosensitive channels may be used to sense gentle touch versus noxious mechanical stimuli.